Securitization: The Concept and Its Relevance to Indian Banks - Singh, Dharmendra; Malik, Garima Kohli (Indian Journal of Finance, 2007)
The recent past has seen financial innovation in the international and the domestic market. Products and techniques like factoring, Value at risk (VaR) is becoming common in view of the changing needs of borrowers and lenders. The liberalization led to the integration of capital market, money market and debt market to the global financial market. The deepened and widened integrated financial market solely cannot rely on the conventional ways and means of financing that is why there are continuous innovations in terms of Instruments, Intermediation and Institutions. One of the most discussed about and sought after innovation is Securitization. Assets Securitization is gaining more popularity as a result of expansion of financial market. This present paper is an attempt to find out how the securitization could be instrumental to transform illiquid assets into liquid or marketable assets and how it is useful to Indian banks in the era of consolidation and cut throat competition.